Training on seed quality testing for conservation, distribution and use of genetic resources to enhance food system transformation - Olbana, Tamiru; Dawit, Woubit; Habte, Ermias; Fentahun, Mekuanent; Negawo, Alemayehu T. (International Livestock Research Institute, 2025)
The five-day training took place at the ILRI Forage Genebank in Addis Ababa from 19–23 May 2025. Thirteen participants, comprising six staff members from the EAA and seven from the EBI attended the training. The training focused on seed quality testing and aimed at enhancing the participants' understanding and skills in this critical area.